2014
DOI: 10.1016/j.expneurol.2014.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Decreased SIRT2 activity leads to altered microtubule dynamics in oxidatively-stressed neuronal cells: Implications for Parkinson's disease

Abstract: The microtubule (MT) system is important for many aspects of neuronal function, including motility, differentiation, and cargo trafficking. Parkinson’s disease (PD) is associated with increased oxidative stress and alterations in the integrity of the axodendritic tree. To study dynamic mechanisms underlying the neurite shortening phenotype observed in many PD models, we employed the well-characterized oxidative parkinsonian neurotoxin, 6-hydroxydopamine (6OHDA). In both acute and chronic sub-lethal settings, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 92 publications
(126 reference statements)
2
28
0
1
Order By: Relevance
“…Sirtuin 2 (SIRT2), an additional tubulin deacetylase has been shown to interact with soluble heterodimers as well as assembled microtubules [92]. Interestingly, the oxidative neurotoxin 6-hydroxydopamine (6OHDA) was shown to influence SIRT2 activity and microtubule dynamics through more than one mechanism, leading to impaired nuclear import of certain transcription factors [93, 94]. Consistently, altered subcellular localisation of transcription factors has been reported in post-mortem PD brains [93, 95, 96].…”
Section: Microtubulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sirtuin 2 (SIRT2), an additional tubulin deacetylase has been shown to interact with soluble heterodimers as well as assembled microtubules [92]. Interestingly, the oxidative neurotoxin 6-hydroxydopamine (6OHDA) was shown to influence SIRT2 activity and microtubule dynamics through more than one mechanism, leading to impaired nuclear import of certain transcription factors [93, 94]. Consistently, altered subcellular localisation of transcription factors has been reported in post-mortem PD brains [93, 95, 96].…”
Section: Microtubulesmentioning
confidence: 99%
“…In all cases, deacetylase inhibitor therapy resulted in symptomatic alleviation. However, it should be noted that oxidative stress induced by the neurotoxin 6OHDA also reduces deacetylase activity via inhibition of SIRT2 [94]. This finding indicates that therapeutic effects of deacetylase inhibition may be context-dependent.…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Several experimental studies have suggested that SIRT2 reduction can produce beneficial effects on Parkinson's disease (PD) . Because cumulative evidence has indicated critical roles of oxidative stress in the pathogenesis of PD and other neurological diseases , it is of importance to investigate the potential relationship between SIRT2 and oxidative stress.…”
mentioning
confidence: 99%
“…SIRT2 has been reported to deacetylate α-tubulin, in an NAD + dependent manner (262,263). Changes in SIRT2 activity have been linked to altered microtubule dynamics (264). Further, agents that alter tubulin-mediated intracellular transport of DNA repair proteins worsen DNA damage repair (265).…”
Section: Future Directionsmentioning
confidence: 99%